Ultrasound for monitoring twin cesarean scar pregnancy following feticide - Chong, Yiwen; Wang, Wei; Zhang, Aiqing; Zhao, Yangyu (Journal of international medical research, 2022)
Objective Implantation of the conceptus in a twin cesarean scar pregnancy (CSP) is considered the rarest type of ectopic pregnancy. Preserving the fetus in utero and effectively dealing with CSP can be challenging. This study aimed to determine the clinical value of ultrasonography by monitoring imaging changes in twin CSP following selective feticide. Methods Ultrasonographic and clinical data were collected from four patients with twin CSP who were treated between December 2017 and December 2018 at our hospital. Results All patients had a history of cesarean section, followed by a heterotopic CSP, with one embryo implanted into the uterine cavity and the other located in the anterior isthmus. All of the patients were pregnant with twins with double chorionic and amniotic sacs, and all gave birth in our hospital. The patients underwent feticide at 8 to 9 weeks of gestation, after which we focused on monitoring the implantation. Delivery was performed by cesarean section according to scores of an ultrasonic scoring system and clinical manifestations. The patients’ uterus was preserved and they recovered. Conclusions This study shows that ultrasound is useful for determining the timing of clinical termination of CSP by selective feticide.